2020
DOI: 10.3390/medicina56080371
|View full text |Cite
|
Sign up to set email alerts
|

A Hospital Protocol for Decision Making in Emergency Admission for Acute Diverticulitis: Initial Results from Small Cohort Series

Abstract: Background and objectives: We present initial results from a small cohort series for a hospital protocol related to the emergency hospitalization decision-making process for acute diverticulitis. We performed a retrospective analysis of 53 patients with acute diverticulitis admitted to the Department of Emergency and Trauma Surgery of the “Azienda Ospedaliero Universiaria-Ospedali Riuniti” in Ancona and to the Department of General and Emergency Surgery of the “Azienda Ospedaliera-Universitaria” in Perugia. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Potential explanations are inadequate follow-up or improvements in the commercially available NPWT systems [ 67 ]. DCS can also pose a significant burden on hospital resources and increases the cost of the treatment [ 68 ]. None of the studies included in this review reported a cost analysis, which is another limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Potential explanations are inadequate follow-up or improvements in the commercially available NPWT systems [ 67 ]. DCS can also pose a significant burden on hospital resources and increases the cost of the treatment [ 68 ]. None of the studies included in this review reported a cost analysis, which is another limitation.…”
Section: Discussionmentioning
confidence: 99%